NEGATIVE BEHAVIOUR THREATS IN DECISION-MAKING PROCESS OF MANAGEMENT ACCOUNTING - Nayel, Khalid (International Journal For Research In Business, Management And Accounting, 2020)
Human behaviour has been considered as a fundamental factor in influencing the quality of management accounting roles including decision-making process as a significant aspect in this field. This research focuses on the negative impact of human behaviour on decision-making process, and shows the possible threats which could affect the main stages. The possible threats of behavioural factors on decision-making are introduced through three sections. The most influential behavioural factors highlighted in this research are personality, job satisfaction and the weakness of administrative leadership. This research attempts to provide a critical view of the underlying negative implications of these behavioural factors through presenting and linking them with the main stages of decision-making processes.